CHRONIC WOUND MANAGEMENT – TRADITIONAL AND CONTEMPORARY THERAPEUTIC APPROACHES - Bartłomiej Siuzdak; Aleksandra Piech; Wiktoria Mika; Karolina Pasierb; Tomasz Ufniarski; Maria Ufniarska; Aleksandra Markuszewska; Weronika Grodzińska; Piotr Sobkiewicz; Karol Poplicha; Marta Jutrzenka (International Journal of Innovative Technologies in Social Science, 2026)
Chronic wounds are a significant clinical and socioeconomic burden, causing major health concerns and associated costs in terms of quality of life. Conventional solutions like debridement, gauze dressings, systemic antibiotics and offloading continue to be widely used due to their accessibility and low cost, although they may not be adequate for advanced or long-standing cases. This manuscript reviews and contrasts traditional and novel management techniques in chronic wound care. Advanced dressings providing a moist environment, negative pressure wound therapy (NPWT) and bioengineered matrices provide better healing, reduced infection risk, and lower long-term costs than other conventional approaches. Smart dressings incorporating biosensors and emerging therapies, such as nanomedicine, stem cells and growth factors, also have great promise, but require large-scale validation. Conventional strategies continue to be useful in initial and less complicated wounds but modern, individualized, and multi-disciplinary care is becoming more important in achieving better outcomes. Integrating both approaches, following EWMA and NICE guidelines, appears most effective to deliver on innovation, accessibility and cost-effectiveness in chronic wound care.Material and method: This study employed a narrative review approach based on the analysis of recent scientific publications, international guidelines (EWMA, NICE), and clinical trial results comparing traditional and modern strategies for the management of chronic wounds.